RANCANGAN ALAT PENGERING IKAN ASIN DAN KERUPUK IKAN DENGAN SISTEM PENGOPERASIAN OTOMATIS - Novavictorianto, Yosef Kurnia; Arifin, Zaenal; Irwan, Hery (University of Riau Kepulauan, 2024)
The coastal area of Tanjung Riau, Sekupang District, Batam City, Riau Islands, is still drying salted fish using conventional methods with drying areas in the form of racks or boards arranged on open land. However, this method has a weakness because the drying process still requires more time, namely 1 to 2 days for drying the fish. If the weather is cloudy and it rains, drying can take 3 to 5 days. The working principle of the Arduino Uno-based automatic salted fish dryer design is to use a heating element as a heating source for the drying rack, and a fan as a stabilizer for air circulation, then a DHT 22 temperature and humidity sensor to find out what the temperature and humidity are in the drying rack, an oled LCD 16x2 which functions to display temperature values, menus and drying time, then Arduino Uno as a microcontroller is programmed to run the system. The design of this tool is 120 cm high, 70 cm wide and 84 cm long. It also has 4 baking pans for drying salted fish and fish crackers, each of which can only accommodate fish and fish crackers weighing 5 kg. The overall test results were carried out by drying 2 types of drying processes, namely drying salted fish and fish crackers. Tests showed that drying salted fish took 7 to 8 hours, and drying fish crackers took 3 to 4 hours.